Study of the effect of Beauveria bassiana (Vuil,) on the biochemistry and structure of the cuticle of Schistocerca gregaria (Forskal) - HALOUANE, F.; Bissaad, F. Z.; Doumandji-Mitiche, B.; Benzina, F.; Chahbar, N.; Hamid, Sonia (Université de Bouira, 2013)
This study was undertaken in order to help identify the biological activity of the entomopathogenic Beauveria bassiana against the cuticle of adult individuals and 5th stage larvae of Schistocerca gregaria viewpoint biochemistry and structure. The application of entomopathogenic B.bassiana with the dose 1.69 × 105 spores / ml on the cuticle of L5 and adults of S.gregaria showed a significant reduction in the dry weight of the cuticle from 36,50mg to 32.93 mg in L5 and 46.49 mg to 42.31 mg in adults. The same is true for the chitin content is increased from 7.38 mg to 6.44 mg in L5 and 7.41 mg to 4.20 mg in adults. For proteins, the amount dropped to 29.12 mg 26.48 mg in L5 and 39.08 mg to 37.88 mg in adults. The larval cuticle of the fifth stage of S.gregaria highlighted by differential staining with Heidenhain azan , shows the presence of the epicuticle , the exocuticle and endocuticle. The epicuticle colored red is as a thin layer on the surface of the cuticle and L5 S. .gregaria exocuticulaire least orange colored thinner than the first part of a colorless and a greater thickness corresponds to the endocuticle. The application of the integument B.bassiana 5th larval stage S.gregaria was dependent of an apparent disturbance on the structure of the cuticle.Indeed the third day of treatment it has been observed a complete disappearance of the epicuticle and a sharp decline in the thickness of the exo and endocuticle and that compared to the control larvae cuticle or three layers are distinct and exposed with a visibly thicker. The breakdown of cuticular layers larvae treated is probably due to degradation by proteolytic enzymes and chitinolytic the infectious unit of our fungal strain, spore which was spotted a few cells in parts of the cuticle digested.
Keywords: Schistocerca gregaria; Beauveria bassiana; cuticle treatment; biological control